2022
DOI: 10.1186/s12903-022-02616-1
|View full text |Cite
|
Sign up to set email alerts
|

The incidence of radicular groove on maxillary lateral incisors of Saudi population: CBCT evaluation

Abstract: Background The radicular groove (RG) is one of the developmental anomalies that is commonly found in maxillary incisors. The formation of radicular groove is initiated around the cingulum and can reach the root at different levels. The incidence of radicular grooves was reported in different countries but there was no published data about the incidence of RG in Saudi Arabia. Therefore, this study aimed to evaluate the incidence of radicular grooves on maxillary lateral incisors in the Saudi pop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 42 publications
(65 reference statements)
1
6
1
Order By: Relevance
“…This was almost like the previous CBCT investigations ( Aksoy et al, 2017 , Arslan et al, 2014 , Ghahramani et al, 2018 , Lekshmi et al, 2021 ). Alkahtany et al ( Alkahtany et al, 2022 ) studied the prevalence of PGG in Saudi patients and found that PGG was present in 13 (4.9%) of the 264 patients, slightly lower than the current study (6.3%). The PGG was more prevailed in the maxillary lateral incisors and this predominance was frequently reported in the previous studies ( Table 1 ).…”
Section: Discussioncontrasting
confidence: 79%
See 2 more Smart Citations
“…This was almost like the previous CBCT investigations ( Aksoy et al, 2017 , Arslan et al, 2014 , Ghahramani et al, 2018 , Lekshmi et al, 2021 ). Alkahtany et al ( Alkahtany et al, 2022 ) studied the prevalence of PGG in Saudi patients and found that PGG was present in 13 (4.9%) of the 264 patients, slightly lower than the current study (6.3%). The PGG was more prevailed in the maxillary lateral incisors and this predominance was frequently reported in the previous studies ( Table 1 ).…”
Section: Discussioncontrasting
confidence: 79%
“…Hou & Tsai, in 1993 ( Hou and Tsai, 1993 ), included the cases with distinct PGG situated at or apical to the cementoenamel junction (CEJ). Several techniques have been used to assess PGG, including in vivo clinical observations ( Al-Rasheed, 2011 , Bačić et al, 1990 , Brin and Ben-Bassat, 1989 , Hamagharib et al, 2015 , Hou and Tsai, 1993 , Iqbal et al, 2011 , Pécora et al, 1992 , Shreshta et al, 2014 , Withers et al, 1981 ), in vitro examinations of extracted teeth ( Albaricci et al, 2008 , Everett and Kramer, 1972 , Kogon, 1986 , Pécora et al, 1991 ), and retrospective assessments of CBCT images ( Aksoy et al, 2017 , Alkahtany et al, 2022 , Arslan et al, 2014 , Ghahramani et al, 2018 , Lekshmi et al, 2021 , Varun et al, 2022 ) ( Table 1 ). Generally, the race and sex of the patients may affect the teeth morphology and prevalence of dental anomalies ( Khalaf et al, 2014 , Martins et al, 2021 , Martins et al, 2018 ); however, Pecora et al & Withers e t al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…examined the maxillary lateral incisors in the Saudi Arabian population and reported a prevalence of PG of 4.9%. [ 14 ] Shreshta et al . reported a 2.4% prevalence of PG in the maxillary canines, in contrast to our study where no PGs were identified in the maxillary canines.…”
Section: Discussionmentioning
confidence: 99%
“…Literature, including case reports, has illuminated RG's role in endodontic-periodontal issues [7-9, 19, 20] and during intentional replantation processes [11]. While CBCT signi cantly enhances root anatomy analysis [5,21], its routine application is curtailed by radiation exposure concerns.…”
Section: Introductionmentioning
confidence: 99%